2016
DOI: 10.15288/jsad.2016.77.249
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Twenty Underage Drinking Laws

Abstract: ABSTRACT. Objective: Over the last two decades, many states have adopted several of the 20 laws that aim to control youth access to and possession of alcohol and prevent underage drinking in the United States. However, many of these laws have not been evaluated since their adoption. The objective of this study was to determine which minimum legal drinking age 21 (MLDA-21) laws currently have an effect on underage drinking-and-driving fatal crashes. Method: We updated the effective dates of the 20 MLDA-21 laws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Percentages of binging at those levels were determined only in the 2013 and 2015 YRBS surveys and did not significantly differ between surveys. Until such questions are routinely collected over longer time periods, research will be unable to assess whether state‐level policies and individual, family, school, and community interventions (DeJong and Blanchette, ; Fell et al., , ; Hawkins et al., ; Hingson and White, ; Komro et al., ; McCartt et al., ; Spoth et al., , ; Tanner‐Smith and Lipsey, ; Turrisi et al., ; Wagenaar et al., ) known to reduce underage drinking can also affect underage binge drinking, particularly at ≥twice the age‐/gender‐specific thresholds, and the related greater likelihood of health‐risk behaviors and consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Percentages of binging at those levels were determined only in the 2013 and 2015 YRBS surveys and did not significantly differ between surveys. Until such questions are routinely collected over longer time periods, research will be unable to assess whether state‐level policies and individual, family, school, and community interventions (DeJong and Blanchette, ; Fell et al., , ; Hawkins et al., ; Hingson and White, ; Komro et al., ; McCartt et al., ; Spoth et al., , ; Tanner‐Smith and Lipsey, ; Turrisi et al., ; Wagenaar et al., ) known to reduce underage drinking can also affect underage binge drinking, particularly at ≥twice the age‐/gender‐specific thresholds, and the related greater likelihood of health‐risk behaviors and consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Hosting of underage drinking parties (laws that impose criminal or other liability against individuals who allow underage drinking events on property they own, lease, or otherwise control) 34, 54 Social host liability (laws that impose civil liability on noncommercial alcohol providers for harms caused by their intoxicated or underage drinking guests) 45,55 Pricing Increasing alcohol tax rates (laws specifying the three major types of taxes levied on beer-"specific excise taxes" (taxes levied on the quantity of a beverage) and "ad valorem excise taxes" and "sales taxes" (taxes levied on the price of a beverage) [56][57][58][59][60][61][62][63][64] Restrictions on drink specials (laws that restrict onpremises retailers from using price-or volume-related marketing tactics such as happy hours, two-for-one specials, and free drinks) 24,65,66 Drinking and Driving Graduated drivers' licenses (laws designed to delay full licensure for teenage automobile drivers through a minimum supervised learners' period or an intermediate license period that limits driving in highrisk situations) 67 Youth BAC limits (laws establishing blood alcohol concentration limits for underage drivers) 8,[68][69][70] A just-published research study provides additional support for many of these policies. Fell et al 71 examined the ratio of drinking to non-drinking drivers in the U.S. in all states from 1982 to 2012 using the Fatality Analysis Reporting System. Structural equation modeling compared drivers aged r20 years versus those aged Z26 years.…”
Section: Social Availabilitymentioning
confidence: 99%
“…Collectively, these nine types of laws prevent 1,135 alcohol-related traffic deaths per year and 210 more lives would be saved annually if all states passed these laws. 71 In light of the evident efficacy of these and other policies, the STOP Act directed the ICCPUD to assess the extent to which policies are being implemented across the country. Detailed descriptions and information on state adoption of these policies are in Chapter 4.3 of the annual Report to Congress.…”
Section: Social Availabilitymentioning
confidence: 99%
“…Today, more than a dozen additional policies targeting underage youth drinking, alcohol providers, and drinking and driving have been adopted to varying degrees and strengths (9). Recent evidence has suggested that stronger policies, rather than just their presence or absence, is associated with lower underage traffic fatality rates and binge drinking (10)(11)(12)(13)(14)(15). However, what remains unclear is the extent to which stronger alcohol policies are related to the prospective risk of underage drinking over time.…”
Section: Introductionmentioning
confidence: 99%